A pilot study of women's affective responses to common and uncommon forms of aerobic exercise. Issue 2 (1st February 2016) - Stevens, Courtney J.; Smith, Jane Ellen; Bryan, Angela D.
Abstract : Objective: To test the extent to which participants exposed to an uncommon versus common exercise stimulus would result in more favourable affect at post-task. Design: Experimental design. Participants ( N = 120), American women aged 18–45 years, were randomly assigned to complete 30-min of either the uncommon (HOOP; n = 58) or common (WALK; n = 62) exercise stimulus. Main outcome measures: Self-reported affect and intentions for future exercise were measured before and after the 30-min exercise bout. Results: Analyses of covariance were run to compare post-task affect across the HOOP and WALK conditions. At post-task, participants assigned to HOOP reported more positively valenced affect, higher ratings of positive activated affect, lower ratings of negative deactivated affect,   and stronger intentions for future aerobic exercise compared to participants assigned to WALK. Conclusions: Participants who completed an uncommon bout of aerobic exercise (HOOP) reported more favourable affect post-exercise, as well as stronger intentions for future exercise, compared to participants who completed a common bout of aerobic exercise (WALK). Future work using a longitudinal design is needed to understand the relationships between familiarity with an exercise stimulus, affective responses to exercise, motivation for future exercise behaviour and exercise maintenance over time.